Trichotillomania and Trichobezoar in Teenager: a Clinical Case - Elena N. Efanova; Yuriy E. Rusak; Alena V. Gorshkova; Ekaterina A. Vasilyeva ("Paediatrician" Publishers LLC, 2019)
Background. Trichotillomania is one of the topical problems in dermatovenerology. Annually the number of people who visit dermatologists with hair loss problem is increasing and makes up to 8-10% in structure of dermatologic illnesses.Clinical Case Description. There are patients with primary psychiatric disorders in practice of dermatologist. This disorders are accompanied by self-injurious behavior and secondary skin changes and/or its appendages. We are performing clinical survey of trichotillomania of hairy part of the head, onychophagy, trichophagy with following developing of trichobezoar in teenage girl. To treat this girl we have carried out surgical operation. Later we have performed complex drug and non-drug treatment under control of pediatric psychiatrist, psychotherapist and dermatologist. The prognosis and perspectives of pathologic process development have been estimated. Possible etiology, clinical signs and dermatological aspects of diagnosis and treatment of disease were discussed.Conclusion. This clinical case has to draw attention of dermatovenerologists, paediatricians, psychiatrists to the problem of factitial dermatitis.